2011
DOI: 10.1103/physrevlett.106.087004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of a Sign-Changing Two-Gap Superconducting Phase in Electron-DopedBa(Fe1xCox)2As2

Abstract: Scanning tunneling spectroscopic studies of BaðFe 1Àx Co x Þ 2 As 2 (x ¼ 0:06, 0.12) single crystals reveal direct evidence for predominantly two-gap superconductivity. These gaps decrease with increasing temperature and vanish above the superconducting transition T c . The two-gap nature and the slightly doping-and energy-dependent quasiparticle scattering interferences near the wave vectors ( AE , 0) and (0, AE) are consistent with sign-changing s-wave superconductivity. The excess zero-bias conductance and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 40 publications
7
25
0
Order By: Relevance
“…9 Similar gap maps have been observed in the iron pnictide family [10][11][12] and in disordered titanium nitride films close to the superconductor to insulator transition.…”
supporting
confidence: 58%
“…9 Similar gap maps have been observed in the iron pnictide family [10][11][12] and in disordered titanium nitride films close to the superconductor to insulator transition.…”
supporting
confidence: 58%
“…5b) exhibits a finite zero bias conductance (ZBC). Such a feature has been observed previously in other Fe-based superconductors20212223242526, even when probed at much lower temperatures than their T c , indicating the ZBC is not due to the thermal broadening effect. It was also shown that spectral features can vary on different reconstructed surfaces in BaFe 2−x Co x As 2 26 suggesting reconstructions may be closely related to the observed ZBC in Fe-based superconductors.…”
Section: Resultssupporting
confidence: 80%
“…As temperature is raised, the dip appearing at approximately ±1.3 mV between the two above-mentioned peaks reaches even negative conductance values. These two observations indicate that SrPd 2 Ge 2 is indeed an s-wave single-gap superconductor, and s ± pairing proposed for the isostructural 122 iron pnictides, 29 which has been associated with unconventional pairing mediated by magnetic fluctuations, is probably absent here.…”
mentioning
confidence: 61%